Biosecurity Practices for Reducing Antimicrobial Use in Commercial Broiler Farms in Korea - Min Beom Kim; Young Ju Lee (The Journal of Poultry Science)
Farm biosecurity is valuable for reducing the indiscriminate use of antimicrobials. However, its relationship with antimicrobial usage can be difficult to assess because of multiple factors. This study evaluated the impact of biosecurity practices on productivity, frequency of antimicrobial use, and development of antimicrobial resistance. Among factors related to biosecurity, mortality rate <2% within one week of age, survival rate >98%, and production index >350 in farms in which: bedding was not reused or only reused once, regular advice and biosecurity training was provided by poultry veterinarians, distinctions between clean and dirty areas were strictly enforced at all times, workers used farm biosecurity manuals, or disinfection guidelines were fully implemented, including cleaning before introducing new flocks and daily disinfection throughout growth, were significantly higher than those in farms without these measures (p < 0.05). The absence of biosecurity practices increased antimicrobial use to one (25.7%), two (39.2%), and three (25.7%) times (p < 0.05). In farms that implemented biosecurity practices, the antimicrobial administration was significantly increased to two times (44.2%) (p < 0.05), with only 17.4% of farms using antimicrobials three times. The prevalence of environmental Escherichia coli resistant to multiple cephalosporins and chloramphenicol, which are not used on broiler farms, was significantly reduced by biosecurity practices (p < 0.05). Our findings indicate that improved biosecurity practices decrease antimicrobial use, decrease the incidence of antimicrobial-resistant bacteria, and help to eliminate resistant bacteria in farm environments.